Elevating Safety and Self-Value: Enhancing Professional Development to Reduce Heavy Vehicle Incidents in the Mining Industry - Vena Jaladara; Sukmawan, Rezkiyantra Fajar; Hadi, Muhammad Septian; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: The mining industry continues to face a significant challenge with the high incidence of accidents involving heavy vehicle operators. Despite advancements in safety technologies and regulations, the frequency of these incidents remains alarmingly high. This perspective aims to explore the underlying reasons for this persistent issue, particularly focusing on the demanding nature of the mining environment and proposes possible solutions to overcome this issue. Content: Professional development is pivotal for enhancing morale and self-value among employees, crucial not only for reducing accidents but also for fostering a culture of safety and operational excellence in mining. Investing in growth enhances individual capabilities and cultivates a supportive work environment. Leadership development is key in nurturing safety champions, equipping supervisors and managers to promote safety, foster accountability, and inspire teams effectively. Mentorship initiatives facilitate knowledge transfer, fostering a supportive environment that enhances morale, job satisfaction, and safety commitment. Integrating workers' self-value into professional development through targeted training, competency assessments, and recognition programs empowers workers to own their safety and contribute positively to the culture. Access to professional development allows employees to shape their careers, enhancing job satisfaction and safety commitment. By prioritizing leadership and self-value alongside technical training, organizations can create a safer, more resilient workforce.